Trace Metal Residues in Swimming Warrior Crab Callinectes bellicosus: A Consumption Risk - Castro-Elenes, Marisol; Rodríguez-Meza, G. Durga; Pérez-González, Ernestina; González-Ocampo, Héctor A. (Frontiers in Environmental Science, 2021)
Trace metal residues in coastal lagoons are bioaccumulated by benthic organisms commercialized and consumed by humans. This study was determined the trace metal residues in the edible tissue of the Callinectes bellicosus crab to evaluate the consumption health risk. Ninety-five C. bellicosus were collected (April 2014 - January 2015) from the Navachiste lagoon, Mexico. The edible tissues' residues of Zn, Fe, Cu, Mn, Cd, Pb, and Ni in the edible tissues were detected, and the highest estimated daily intake (EDI) was for Zn, Fe, and Cu (0.54, 0.19, and 0.19 μg kg-1 day-1, respectively). Results of target hazard quotients (THQ´s < 0.007), hazard index (HI, 0.02), and THQ (0.03 - 6.32), and THQ per sample (MHI) (98% of samples MHI > 1), revealed significant risk including carcinogenic and non-carcinogenic risks, being the surrounding agricultural and aquaculture activities are the potential sources.